Clinical, Electrophysiological, and Serological Evaluation of Patients with Cramp-Fasciculation Syndrome - MATUR, ZELİHA; Poyraz, Muruvvet; Matur, ZELİHA; Aysal, Fikret; TÜZÜN, Erdem; Hanoglu, Lutfu; ÖGE, Ali Emre (My University, 2017)
Introduction: Cramp-fasciculation syndrome (CFS) is a rare peripheral nerve hyperexcitability syndrome. There are only a few reports on clinical and serological profile of a CFS cohort that was followed up by a single outpatient clinic.